Microglia in Alzheimer’s disease: pathogenesis, mechanisms, and therapeutic potentials - Miao, Jifei; Ma, Haixia; Yang, Yang; Liao, Yuanpin; Lin, Cui; Zheng, Juanxia; Yu, Muli; Lan, Jiao (Frontiers in Aging Neuroscience, 2023)
Alzheimer's disease (AD) is a neurodegenerative disorder characterized by protein aggregation in the brain. Recent studies have revealed the critical role of microglia in AD pathogenesis. This review provides a comprehensive summary of the current understanding of microglial involvement in AD, focusing on genetic determinants, phenotypic states, phagocytic capacity, neuroinflammatory response, and impact on synaptic plasticity and neuronal regulation. Furthermore, recent developments in drug discovery targeting microglia in AD are reviewed, highlighting potential avenues for therapeutic intervention. This review emphasizes the essential role of microglia in AD and provides insights into potential treatments.